Wordwall Platform and Its Effect on Students’ Reading Comprehension - Fitria, Wahyuni; Agustin, Dilla; Saijun (ENGLISH FRANCA : Academic Journal of English Language and Education, 2025)
The effect of the Wordwall platform in enhancing students' reading comprehension was examined in this study, focusing on eighth-grade students at a private Islamic Junior High school in Jambi. A quantitative approach with a quasi-experimental design was employed, involving two groups: an experimental group and a control group, each consisting of 29 students selected through cluster random sampling. Data were obtained through pre-tests and post-tests using short essay questions focused on recount texts. A notable effect in reading performance was observed in the experimental group, which mean score increased from 55.86 to 76.03. Meanwhile, the control group demonstrated a smaller increase, from 57.59 to 69.14. The data met the assumptions of normality and homogeneity, and a statistically significant difference was identified through a post-test t-test (t = 3.699, p = 0.01), indicating that the alternative hypothesis could be accepted. These results suggest that the integration of Wordwall into reading comprehension contributes positively to students’ learning outcomes. Moreover, its interactive features were found to enhance student engagement, indicating that digital tools such as Wordwall can be effectively utilized to support reading comprehension, particularly in junior high school contexts.